Valuación de cartera del Cuerpo de Bomberos de la Ciudad de Quinsaloma en el periodo 2021 – 2022. - Guzmán Gilces, Franklin Alejandro (2023)
The following case study is based on knowing the main causes that have led to the Quinsaloma Fire Department not having a collection management process for the expired portfolio due to operating permits that allows it to maintain adequate resources for its operations, being a first response public law organization, whose mission is to attend to fire emergencies, rescue victims in accidents and floods that occur in the Quinsaloma canton and its surroundings. The portfolio valuation of the Fire Department of the city of Quinsaloma in the period 2021 – 2022 constitutes a tool for decision-making by managers and to be able to apply the necessary corrective measures, focusing on the design of new strategies to combat possible threats and weaknesses. that cause a lack of resources for payroll payment, basic services, vehicle maintenance, firefighting equipment and emergency response. This study case, prepared as part of the graduation requirements of the Accounting and Auditing career, is part of the research line “Financial, Administrative Management, Audit and Control”, framed in the Research Sub-line “Financial Management, Tax and social commitment”.